The Evolution of Digital Dentistry: A Comprehensive Review - Nishad Gawali; Priti P. Shah; Inderjit M. Gowdar; Kevalkumar A. Bhavsar; Debanti Giri; Rashmi Laddha (Wolters Kluwer Medknow Publications, 2024)
Digital dentistry has revolutionized the traditional practice of dentistry, offering new tools and technologies that enhance diagnosis, treatment, and patient care. This comprehensive review explores the evolution of digital dentistry, its role in modern dental practice, and the advantages, limitations, and future prospects. By examining the current state of digital dentistry, this review aims to provide insights into its transformative impact on dental healthcare.